Research for change: The Jameel Observatory for Food Security Early Action - Jameel Observatory for Food Security Early Action (University of Edinburgh, 2024)
In the drylands of East Africa, pastoralist communities face the brunt of environmental shocks and stresses, threatening their food security and livelihoods. These communities are resilient and adaptable, having dealt with drought and other calamities for hundreds of years. Today, though, even their adaptability is stretched to breaking points.